Comparison of behavioural and molecular effects of two different schizophrenia models induced by subchronic MK-801 administration in rats - ARICIOĞLU, FEYZA (MARMARA UNIV, FAC PHARMACY, 2018)
Schizophrenia is a severe psychiatric disorder with about 1% prevalance. NMDA receptor antagonists such as Phencyclidine (PCP) and MK-801 are commonly used for modeling schizophrenia in rodents. In literature, despite of the concensus about subchronic PCP administration (commonly 7 days, bi-daily administration followed by a 1 week washout period), there are different subchronic administration regimens for MK-801 beside 7 days, bidaily (MK-801-7), such as 14 days (MK-801-14) daily or 28 days daily injections. In this study, we aimed to compare two prevalant MK-801 models (MK-801-7 and MK-801-14, 0.2 mg/kg)in both behavioural and molecular changes. Wistar Hannover rats grouped as control (n=10), MK-801-14 (n=8) and MK-801-7 (n=8). Prepulse inhibition of acustic startle response (PPI), novel object recognition test (NORT), social interaction (SI) and Morris's water maze (MWM) tests were used for behavioural analyzes while real time polimerase chain reaction (Rt-PCR) was conducted for molecular analyzes of glutamic acid decarboxilase 67 (GAD67) and parvalbumin. Our results showed decreased PPI in MK-801-14 and MK-801-7 groups. Moreover, in both models platform finding latencies were increased and swimming time in platform area was decreased in MWM. MK-801-14 and MK-801-7 reduced following and raised avoiding behaviours in SI. In Rt-PCR, GAD67 mRNA levels were decreased by MK-801-14 and MK-801-7 administrations. However, only MK-801-7 decreased discrimination index in NORT and parvalbumin mRNA levels. In this study, it has been showed that although MK-801-14 and MK-801-7 administrations revealed smiliar schizophrenia like symptoms in rats, MK-801-7 has partial superiories in certain aspects.
Keywords: MK-801; GAD67; Parvalbumin; Schizophrenia; NMDA RECEPTOR SUBUNITS; MORRIS WATER MAZE; NEGATIVE SYMPTOMS; COGNITIVE DYSFUNCTION; RECOGNITION MEMORY; DEFICITS; PHENCYCLIDINE; ANTIPSYCHOTICS; MECHANISMS; EXPRESSION